2015
DOI: 10.3390/cancers7010407
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Institutional Comparison of Personalized Risk Assessments for Second Malignant Neoplasms for a 13-Year-Old Girl Receiving Proton versus Photon Craniospinal Irradiation

Abstract: Children receiving radiotherapy face the probability of a subsequent malignant neoplasm (SMN). In some cases, the predicted SMN risk can be reduced by proton therapy. The purpose of this study was to apply the most comprehensive dose assessment methods to estimate the reduction in SMN risk after proton therapy vs. photon therapy for a 13-year-old girl requiring craniospinal irradiation (CSI). We reconstructed the equivalent dose throughout the patient’s body from therapeutic and stray radiation and applied SMN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 42 publications
(66 reference statements)
1
18
0
Order By: Relevance
“…Mu et al [21] noted that the mean lung dose was not significantly reduced with PrT. This was later supported by Zhang et al [20] and Taddei et al [27] who concluded that SMR after PrT was generally reduced with the exception of the lungs. Girls were found to have higher LAR of lung cancer than boys resulting from a greater proportion of their lungs received more dose due to their smaller physical stature, as mentioned previously.…”
Section: ããmentioning
confidence: 90%
See 2 more Smart Citations
“…Mu et al [21] noted that the mean lung dose was not significantly reduced with PrT. This was later supported by Zhang et al [20] and Taddei et al [27] who concluded that SMR after PrT was generally reduced with the exception of the lungs. Girls were found to have higher LAR of lung cancer than boys resulting from a greater proportion of their lungs received more dose due to their smaller physical stature, as mentioned previously.…”
Section: ããmentioning
confidence: 90%
“…Eight of fifteen articles [20][21][22][25][26][27][28][29]] that compared SMR between Proton-and Photon-CSI, highlighted that Proton-CSI yielded lower SMR for most organs when compared to 3DCRT, IMRT and VMAT (Table 4 and supplementary appendix C). VMAT and IMRT led to highest SMR amongst all radiation techniques [21,22,29].…”
Section: Risk Of Second Malignancy Following Proton and Photon Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…( 38 ). An empirical model was developed for photon CSI ( 93 , 94 ) to model out-of-field radiation exposures. That model parameterized measured data in an approach conceptually similar to that of Stovall et al ( 95 ).…”
Section: Recent Advances In Research Methodsmentioning
confidence: 99%
“…In an effort to balance speed, accuracy, and available resources, Taddei et al (2013) created an anthropomorphic measurement-based analytical model to accurately estimate the out-of-field dose for children receiving craniospinal irradiation (CSI). They later applied this model in subsequent studies that compared risks of SMNs in proton CSI versus photon CSI (Taddei et al 2015, Taddei et al 2018). This approach was innovative in that a computationally inexpensive and fast method to calculate out-of-field dose could be applied to many patients if missing anatomy were made available.…”
Section: Introductionmentioning
confidence: 99%